2001
DOI: 10.1103/physrevlett.86.3891
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Rotation via a Monoclinic Phase in the Piezoelectric 92%PbZn1/3Nb2/3O

Abstract: Polarization Rotation via a Monoclinic Phase in the Piezoelectric 92%PbZn1/3Nb2/3O3-8%PbTiO3 Noheda, Beatriz; Cox, D.E.; Shirane, G.; Park, S.-E.; Cross, L.E.; Zhong, Z.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

32
410
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 680 publications
(445 citation statements)
references
References 19 publications
32
410
1
2
Order By: Relevance
“…In this article, we present the discovery of an interesting topological form in ferroelectrics, found in situations where both of the above environmental influences are in PZN-12PT is a tetragonal dipolar perovskite oxide, with a composition close to a morphotropic phase boundary (MPB) between a number of different symmetry states [27][28][29].…”
mentioning
confidence: 99%
“…In this article, we present the discovery of an interesting topological form in ferroelectrics, found in situations where both of the above environmental influences are in PZN-12PT is a tetragonal dipolar perovskite oxide, with a composition close to a morphotropic phase boundary (MPB) between a number of different symmetry states [27][28][29].…”
mentioning
confidence: 99%
“…1-3 Similar enhancements in the electromechanical properties were also reported 4 when crystals were poled at finite angles with respect to the ͗001͘, although the coupling factors of these finite miss-oriented crystals were lower ͑ϳ0.8͒. [5][6][7] Investigations have demonstrated the presence of monoclinic (FE m ) and orthorhombic (FE o ) ferroelectric states inbetween the FE r and tetragonal ferroelectric (FE t ) phases. [5][6][7] The result opens an interesting possibility that intermediate states may be responsible for the high electromechanical performance.…”
mentioning
confidence: 77%
“…[5][6][7] Investigations have demonstrated the presence of monoclinic (FE m ) and orthorhombic (FE o ) ferroelectric states inbetween the FE r and tetragonal ferroelectric (FE t ) phases. [5][6][7] The result opens an interesting possibility that intermediate states may be responsible for the high electromechanical performance. First principles calculations have indicated that the transformation under electric field between FE r and FE t proceeds by a rotation of the polarization between ͗111͘ and ͗001͘.…”
mentioning
confidence: 99%
“…Therefore, by making the field induced phase transition to occur at significantly lower electric fields and at much faster rates would make it possible to create a material with high effective piezoelectric properties. Recently, it was shown that domain-engineered relaxor-FE crystals with 4 mm and 2 mm macrosymmetries exhibited a large and reversible phase transformation strain under mechanical compression that is tunable by an electric field [7][8][9]13]. A very sharp hysteretic quasistatic strain curve and polarization jumps accompanied by a dramatic change in stiffness (by a factor of 6-8) at stress less than 15 MPa have been reported first in the PZN-PT crystals [7].…”
mentioning
confidence: 99%
“…In the early 1980's Kuwate et al [5] discovered the extraordinary high electromechanical properties in relaxor-FE lead zinc niobate (PZN)-lead titanate (PT) single crystals, for compositions on the rhombohedral side of the morphotropic phase boundary (MPB), with piezoelectric coefficients of d 33 >1500 pm V À1 , and electromechanical coupling of k 33 ¼ 0.92. This discovery was revived by a significant research effort in the mid 1990's in relaxor-FE single crystals [6], particularly in binary systems with the general formula (1 À x)Pb(B I 1/3 Nb 2/3 )O 3 -(x)PbTiO 3 , where B I can either be Zn or Mg, and more recently, work was focused on ternary lead indium niobate (PIN)-lead magnes-ium niobate (PMN)-PT [7][8][9][10][11]. As a result, sound projectors fabricated from PMN-PT single crystals offer nearly triple the bandwidth, and an order of magnitude higher acoustic power than that of standard PZT projectors because of their significantly higher coupling factor and piezoelectric coefficient [9].…”
mentioning
confidence: 99%